2017
DOI: 10.3390/ijerph14020122
|View full text |Cite
|
Sign up to set email alerts
|

General Population Knowledge about Extreme Heat: A Cross-Sectional Survey in Lisbon and Madrid

Abstract: Extreme heat is associated with an increased mortality and morbidity. National heat plans have been implemented to minimize the effect of extreme heat. The population’s awareness and knowledge of national heat plans and extreme heat is essential to improve the community’s behavior and adaptation. A general population survey was conducted in Lisbon and in Madrid to assess this knowledge. We used a questionnaire to interview passers-by. Results were compared between Lisbon and Madrid and between locals and forei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 20 publications
4
22
0
Order By: Relevance
“…Most heat stressed respondents experienced light symptoms, mostly fatigue and headaches, as shown in previous studies from Australia [ 36 , 37 ] and Europe [ 38 , 39 ]. The more severe symptoms such as dizziness, skin rashes, confusion and nausea were mainly reported by those with high levels of heat stress.…”
Section: Discussionsupporting
confidence: 72%
“…Most heat stressed respondents experienced light symptoms, mostly fatigue and headaches, as shown in previous studies from Australia [ 36 , 37 ] and Europe [ 38 , 39 ]. The more severe symptoms such as dizziness, skin rashes, confusion and nausea were mainly reported by those with high levels of heat stress.…”
Section: Discussionsupporting
confidence: 72%
“…5 6 The public also appears largely unaware of the risks of heat exposure during pregnancy. 7 Several factors could account for the relative neglect of maternal and newborn health in research and policies on the impacts of, and adaptation to, climate change. Perhaps most notably, challenges with the measurement of exposures and adverse outcomes in maternal and newborn health make it difficult to attribute a single cause, such as heat exposure, to an outcome.…”
Section: Introductionmentioning
confidence: 99%
“…Similar approaches were followed in Florida by Raghavendra et al [ 29 ], where it was shown that the shift in the mean temperature may increase the intensity of future heatwaves by 3–4 °C, while a flattening of the temperature distribution may enhance the intensity by an additional 1–2 °C The research on general knowledge showed that a large proportion of the participants (80%) think that temperatures in Slovenia will rise. In Madrid, 13% of respondents observed no increase in air temperatures, and in Lisbon that was as high as 23% [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, a national survey found that 55% of participants had heard of heat protection recommendations during the 2013 heat wave in the UK [ 30 ], while in Slovenia only 9% had never heard of heat warnings. Questions in the survey were from the questionnaire used in Brussels (among 120 passers-by) and Amsterdam (133) in summer 2015 [ 25 ], and in summer 2016 in Lisbon (129 passers-by) and Madrid (131) [ 26 ]. An important piece of information in Slovenia was that older people reported less thirst as a heat stress symptom than younger people, and also less often reported drinking more fluids.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation